Tradisi Ngusaba Gedebong Sebagai Media Penyuluhan Nilai-Nilai Tri Kerangka Dasar Agama Hindu Terhadap Masyarakat - Ni Ketut Listriani (Jurnal Penelitian Agama Hindu, 2019)
The activities of community life in Bali have never been separated from a religious tradition. Disseminating knowledge about tradition requires a special method. Hinduism provides religious knowledge to its people by carrying out religious counseling programs, which are expected to provide more knowledge and can enlighten the people in need, considering that there are many people who do not understand the meanings contained in the traditions that exist in their respective regions. In addition to face-to-face or verbal methods, counseling or lighting can also be done through ceremonies as an extension media. One of them is through the implementation of tradition, namely the Ngusaba Gedebong tradition which is located in Ngis Village, Manggis District, Karangasem Regency. The Ngusaba Gedebong tradition has a meaning as an expression of gratitude to the goddess Sri as the goddess of fertility for her abundant natural gifts. The problems discussed are the first regarding the process of implementing the Ngusaba Gedebong tradition in Pakraman Ngis Village, Manggis District, Karangasem Regency is dissected using religious theory, the results of the research include the history, time and place of implementation, means of upakara, and a series of Ngusaba Gedebong traditions. Second, the tri values ​​of the basic framework of Hinduism in the Ngusaba Gedebong tradition in Pakraman Ngis Village, Manggis District, Karangasem Regency were dissected using value theory, the results showed that the Ngusaba Gedebong tradition contained tattwa values, moral values ​​and programs that could lead people to do deeds. based on the teachings of Hinduism. Third, regarding the impact of the Ngusaba Gedebong tradition for the people of Pakraman Ngis Village, Manggis District, Karangasem Regency was dissected using effect communication theory, with the results of the discussion including cognitive impacts (changes in knowledge), affective effects such as changes in emotions and feelings, and related behavioral / psychomotor effects. on changes in community behavior.